Pengaruh Pemberdayaan Perempuan Terhadap Peningkatan Ekonomi Produktif - Ninies Eryadini; Nurdiana Ratna; Alfarucha Fitrotun Nufus (Academia Publication, 2021)
This study aims 1) to find out how women’s empowerment is carried out in Balai Sakinah Aisyiyah, 2) to determine the effect of women’s empowerment on increasing the productive economy in Balai Sakinah Aisyiyah’s programs (BSA). Respondents used in the study amounted to 30 membersof Balai Sakinah Aisyiyah.Dta collection methods used in this research are questionnaire and documentationmethods. This research uses a quantitative approach with inferential analysis with a simple linear regression model with the help of SPSS 23. Significance is written by default as 0,05 (5%). Research result are:1) after participating in coaching The Balai SakinahAisyiyah’s programs, members get useful result, namely the knowledge and the economic aspect. 2) from the analysis, it was obtained that the R square value or the coefficient of determination (KD) was 0,344, which means that women’s empowerment had an effect on increasing the productive economy by 34% and the remaining 66% was influenced by other factors. Sig 0,001 which means that the probability value is smaller than 5%, namely 0,05, identifies that women’s empowerment has an effect on the productive economy.